“in”visibility of sexuality themes in school and teacher formation environment (Revista Internacional de Formação de Professores, 2018)
In school, the sex and sexuality subject still consist nowadays in just information exposition, without a problematizing and conscious position being assumed. So, this study aims to discuss the ongoing negation of the LGBTs student in school space and the invisibility of the subject on the continuous formation of the teachers. In order to do it, a brief critical revision of literature was done, we also did a brief analysis of Parâmetros Curriculares Nacionais (PCN) and the approval of the new Base Nacional Comum Curricular (BNCC). We point out the need of questioning the pedagogical practices which did not follow what was proposed by one of PCNs transversal themes, Sexual Orientation. We also reflected on the historical context of a global phenomenon of the actual resurgence of conservatism, which brought regress on the sexual and reproductive rights agenda, above all driven by the incidence of religious speech in politics. We can notice that even with several prejudices and taboos related to sexuality, still is possible to work Sexual Education in class through some viable activities and also can further support the theme with didactical resources, students sensibilization and reflective practices.
Keywords: Sexual diversity. School. Teachers formation. LGBTs. Sexuality.